2023
DOI: 10.1021/acschemneuro.2c00642
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neurotoxicity Screen of Psychedelics and Other Drugs of Abuse in Larval Zebrafish (Danio rerio)

Abstract: In recent years, psychedelics have garnered significant interest as therapeutic agents for treating diverse neuropsychiatric disorders. However, the potential for these compounds to produce developmental neurotoxicity has not been rigorously assessed, and much of the available safety data is based on epidemiological studies with limited experimental testing in laboratory animal models. Moreover, the experimental safety data available thus far have focused on adult organisms, and the few studies conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The potential developmental neurotoxicity of LSD, psilocybin, and DMT was evaluated in the larval zebrafish ( Danio rerio ) model (Tombari et al, 2023). None of the compounds caused statistically significant teratological effects or changes in photomotor behavior; however, LSD was shown to increase anxiety‐like behavior in zebrafish embryos, typically observed as erratic movements, after acute and chronic exposure (Tombari et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The potential developmental neurotoxicity of LSD, psilocybin, and DMT was evaluated in the larval zebrafish ( Danio rerio ) model (Tombari et al, 2023). None of the compounds caused statistically significant teratological effects or changes in photomotor behavior; however, LSD was shown to increase anxiety‐like behavior in zebrafish embryos, typically observed as erratic movements, after acute and chronic exposure (Tombari et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly analysed parameters in larval behavioural tests include total time of motion, distance travelled, speed, acceleration, freezing in light or dark conditions. Many neurotoxic substances, including acrylamide ( Park et al, 2021 ), 6-hydroxydopamine ( Zhang et al, 2017 ), 3,4-methylenedioxyamphetamine ( Tombari et al, 2023 ), fenpropathrin ( Yu et al, 2022 ) have been shown to reduce larval motor activity.…”
Section: Behaviourmentioning
confidence: 99%
“…Larval zebrafish have also been used to screen the behavioral effects of stress exposure, antidepressants, and genetic mutations [ 33 36 ]. However, few published studies have examined or discussed the possible behavioral effects of psychedelics in larval zebrafish [ 37 39 ], and, to date, there have been no reports on detailed behavioral effects of psilocybin. Such scarcity of behavioral insights impedes further research into their actions in neural circuit dynamics.…”
Section: Introductionmentioning
confidence: 99%